Penyuluhan Diversifikasi Produk Aren Melalui Pemanfaatan Mesin Pengupas Aren Modern di Desa Onan Lama - Winfrontstein Naibaho; Jhon Sufriadi Purba; Joupindo Ompusunggu; Adon Agustian Tampubolon; Rio Rosfer Sirait (Jurnal Medika: Medika, 2026)
Onan Lama Village has abundant natural resources in the form of sugar palm (aren), yet its utilization remains limited to traditional products with relatively low added value. The main problems faced by the community include a lack of knowledge regarding product diversification and limited processing technology, particularly in the peeling process, which is still carried out manually, making it inefficient and time-consuming. This Community Service Program aims to improve community knowledge and skills through counseling on sugar palm product diversification and the application of a modern sugar palm peeling machine. The methods employed in this program include socialization, training on machine operation, and direct assistance to community groups. The activities were also complemented by demonstrations of processing sugar palm into various value-added products, such as palm sugar, kolang-kaling, and other derivative products. The results indicate an increase in community understanding of the potential for sugar palm product diversification, as well as improved work efficiency through the use of a modern peeling machine, which accelerates the processing time and reduces labor intensity. This program is expected to enable the community of Onan Lama Village to develop sugar palm-based enterprises more optimally, increase the economic value of their products, and promote community economic independence. Furthermore, the implementation of this appropriate technology is expected to be sustainable and serve as a development model for other regions with similar potential.